FEATURES OF MORPHOLOGICAL CHANGES IN THE SKIN DURING WOUND HEALING - Pavlov, Serge; Kumetchko, Marina; Litvinova, Olga; Babenko, Nataliia; Valilshchykov, Nikita; Semko, Natalia; Shamas, Odday (Journal of Morphological Sciences, 2019)
Concomitant diseases can cause a violation of the orderly and timely course of the wound healing process, which dramatically increases the risk of chronic wounds. Currently, there are only a small number of studies studying the relationship between chronic kidney disease and impaired wound healing. The aim of our work was to study the peculiarities of the morphological changes of the skin during the healing of wounds complicated by chronic kidney disease in the experiment. Studies were performed on 48 white rats. Animals were divided into two groups: control and experimental (rats with chronic kidney disease (CKD)). A model of a chronic wound was reproduced in animals of both groups. On the 7th, 15th and 28th days after the application of wounds, 6 rats from each group were removed from the experiment. Histological examination were subject to skin samples of animals of both groups. To assess the dynamics of wound area reduction, digital macro photography of the wound surface was performed. The results of histological studies indicate an increase in the time course of the phases of inflammation, as well as the imposition of phases on each other. Measurement of the area of the wound surface revealed a slowdown in the process of reducing the area of wounds at all stages of healing in animals with CKD compared with intact animals. Differences in the structure of the tissue are detected even after the completion of the wound healing process in both groups. The results of our study confirm the significant effect of CKD on wound healing. A prolongation of the inflammatory stage of healing is observed, which leads to disruption of the normal epithelialization of the wound and slower maturation of granulation tissue in experimental animals.